Medical and Social Aspects of Alcohol Consumption - Onaca, Emil; Pop, Sorina; Oprea, Radu; Marginean, Codruţa (Medicine and Pharmacy Reports, 2014)
The permissive attitude of society towards alcohol consumption has favored its expansion in time which, supported by advertising and the easy access to alcohol, eventually included all socio-economic categories and increasingly younger age groups. The medical, social and economic consequences of alcohol consumption concern not only the consumers themselves, but also the people surrounding them and society in general. The recommendation of moderate alcohol consumption for cardioprotection is based on empirical criteria, without the possibility of its individualization depending on the receptivity of a particular person to the effects of alcohol. With the appearance of the drinking habit, the risk to pass from the social pleasure of alcohol consumption to the lack of interest in oneself, one’s family, professional activity etc. increases, resulting in health impairment.